Configuration of antenna arrays and effectiveness of adaptive systems - Ковалевський, Е.О. (Proceedings of National Aviation University (archive), 2007)
The detailed analisis and simulation results are presented for the influence of aerial array parameters on the noise rejection in adaptive systems.